The rhetorics of US immigration : identity, community, otherness - Hartelius, E. Johanna, 1979- (The Pennsylvania State University Press, 2015)
"Examines U.S. immigration as a rhetorical process inventing persons and communities in reference to space and place. Engages immigration in media and popular culture; the construction of immigrant experiences in public discourse; and the effects of fear, violence, and exclusion on immigrant and non-immigrant communities"--Provided by publisher